LEXICON OF ABU ALI IBN SINA’S "LAWS OF MEDICINE". - Bakhriyeva Umriniso Maksud kizi (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Abstract: In this article, we will explore the key terms and concepts of Abu Ali Ibn Sina's Laws of Medicine in order to explore the depth of his medical knowledge and the continuing relevance of his teachings in the field of medicine. By examining these basic principles, we can gain an understanding of Ibn Sina's holistic approach to health care and appreciate his contribution to the development of medical science.